(untitled) (International Journal of Engineering and Computer Science, 2015)
Cloud is capable of running many kinds of applications. Putting application to some clouds are free and had their own procedure. Few clouds are famous for their services and OPENSHIFT, a Red Hat Cloud, is one of that cloud service provider which is constantly providing good services thus famous one for individual application deployment. Keeping personal development in mind here we are describing complete procedure to deploy application to OPENSHIFT cloud. For deployment first create a small application in HTML or PHP then application is connected to the newly created GIT repository. GIT repository is then connected to the OPENSHIFT account. Cloud deployment will provide a link which can be used to access your application. Application is successfully running over cloud thus availability to your project anywhere. Deploying application to cloud will provide the access anywhere ease. This deployment will teach the procedure to manage big applications and also this procedure will reflect immediate change in cloud when applications edited at local machine. This will help developers, researcher, and student to start with the very popular concept of cloud.